2006
DOI: 10.1007/s10147-006-0591-4
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous regression of hepatocellular carcinoma

Abstract: We report four patients with hepatocellular carcinoma (all men, with liver cirrhosis and hepatitis C virus infections) who showed spontaneous regression of the tumor. When the spontaneous regression occurred all of the patients were over age 67 years. They showed a rapid increase of serum alpha-fetoprotein levels just before the spontaneous regression of hepatocellular carcinoma. In all the patients, the alpha-fetoprotein level decreased to within normal limits and the tumor was partially to completely reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Sorafenib targets VEGF-mediated angiogenesis (5), which suggests the role of sorafenib in upregulating the immune system (28). Immunological factors may play an important role in this rare phenomenon; however, to date, this role remains incompletely understood (29).…”
Section: Discussionmentioning
confidence: 99%
“…Sorafenib targets VEGF-mediated angiogenesis (5), which suggests the role of sorafenib in upregulating the immune system (28). Immunological factors may play an important role in this rare phenomenon; however, to date, this role remains incompletely understood (29).…”
Section: Discussionmentioning
confidence: 99%
“…This is noteworthy because several studies have found that patients with reported exceptional recoveries have used CAM. For example, Kondo et al 13 mention the use of several unspecified CAM by a patient in a case study of spontaneous regression from hepatocellular carcinoma. Cunningham and Watson 17 also found that patients with reported exceptional recoveries had practiced meditation, which they classified as a "self-help technique," although National Center for Complementary and Alternative Medicine classifies this as CAM.…”
mentioning
confidence: 99%
“…Within biomedical literature, exceptional cancer survival is often discussed in terms of "spontaneous regression" (also called "spontaneous remission"), which Papac called "one of the most fascinating phenomena observed in medicine" 10(p395) and defined as "the complete or partial disappearance of malignant tumour in the absence of therapy that is capable of inducing anti-neoplastic effects." 10(p395) Spontaneous regression has been studied and documented in literature reviews, 11,12 case studies, 13 and theoretical discussions. 10 Spontaneous regression has been reported in relation to nearly all cancer forms, but is said to be more likely to occur in some diagnoses, with renal cell carcinoma, neuroblastoma, and malignant melanoma named as examples.…”
mentioning
confidence: 99%
See 2 more Smart Citations